Spherical Confinement of Chromonics: Effects of a Chiral Aminoacid - Lorenza Spina; Federica Ciuchi; Caterina Maria Tone; Riccardo Barberi; Maria Penelope De Santo (Nanomaterials, 2022)
Induced or spontaneous chirality in natural systems is an intriguing issue. In recent years, a lot of attention has been focused on chirality of chromonic liquid crystals, a class of materials that is able to self-assemble in columnar structures. However, the mechanism involved in the arising of chirality in these materials, that starts at the molecular level and controls the supramolecular structure, is poorly understood; however, it is certainly affected by ionic strength. In this work we present the results obtained doping Cromolyn, a chromonic material, with a strong helical-twisting-power peptide, and confining it in a spherical geometry. We demonstrate, by means of optical polarized microscopy and structural analysis, that both the geometrical constraint and the presence of the chiral dopant enhance the chiral effect; we also demonstrate that they favor the rise of a highly ordered helical superstructure, that may be optimized upon adding an ionic dye to the system. Finally, we report a procedure for the preparation of free-standing polymeric films, embedding and preserving the microspheres, and paving the way for the creation of biocompatible and eco-friendly optical devices to be used in the sensor and anticounterfeiting fields.